High expression of protein tyrosine phosphatase receptor S (PTPRS) is an independent prognostic marker for cholangiocarcinoma - Lertpanprom, Muntinee; Silsirivanit, Atit; Tippayawat, Patcharaporn; Proungvitaya, Tanakorn; Roytrakul, Sittiruk; Proungvitaya, Siriporn (Frontiers in Public Health, 2022)
Cholangiocarcinoma (CCA) is an aggressive tumor of the bile duct with high rate of mortality. Lymph node metastasis is an important factor facilitating the progression of CCA. A reliable biomarker for diagnosis, progression status or prognosis of CCA is still lacking. To identify a novel and reliable biomarker for diagnosis/prognosis of CCA, liquid chromatography-mass spectrometry and tandem mass spectrometry (LC-MS/MS) in combination with bioinformatic analysis was applied for the representative serum samples of CCA patients. The proteome results showed that protein tyrosine phosphatase receptor S (PTPRS) had the highest potential candidate. Then, a dot blot assay was used to measure the level of serum PTPRS in CCA patients (n=80), benign biliary disease patients (BBD; n=39) and healthy controls (HC; n=55). PTPRS level of CCA sera (14.38 ± 9.42 ng/mL) was significantly higher than that of BBD (10.70 ± 5.05 ng/mL) or HC (6.00 ± 3.73 ng/mL) (P< 0.0001). PTPRS was associated with serum albumin (P=0.028), lymph node metastasis (P=0.038), and the survival time of patients (P=0.011). Using a log-rank test, higher serum PTPRS level was significantly (P=0.031) correlated with longer overall survival time of CCA patients, and PTPRS was an independent prognostic marker for CCA superior to carbohydrate antigen 19-9 (CA19-9), carcinoembryonic antigen (CEA) or alkaline phosphatase (ALP). High expression of PTPRS could be a good independent prognostic marker for CCA.